Impact of Training on Awareness of COVID-19 among The Health Care Workers in A Tertiary Care Hospital of Dehradun - Naz, Fouzia; Ohri, Puneet; Sharma, Ashwani; Spandana, B Sudha; Gupta, Kajal (Indian Journal of Community Health, 2022)
Background: Novel Corona virus infection (Covid-19) was declared global pandemic by WHO infecting more than 118,000 cases in 114 countries and the number of deaths counting to 4291. WHO recommends the only strategy to limit the spread of Corona virus is only by prevention itself. Aim and Objective: To assess the awareness among Health Care Workers on covid-19 infection. To compare the level of knowledge among the study participants and To assess the impact of training about the knowledge on covid-19 control. Material and methods: The study was conducted by the Research team of Community Medicine Department, SGRRIM&HS, Dehradun between 1st October to 31st December 2020. Self-administered, pre-tested questionnaire was used to assess the knowledge and awareness among health care workers. Data collected and analysed using SPSS software for different parameters. Result: A total of 421 health care workers participated in the present study. Majority of the study participants were female with 346 (82.2%) while 75 (17.8%) of them were male. Independent t-test was used to compare pre and post test values with Socio-demographic profile, designation, and work place of the respondents. Conclusion: Improvement in the knowledge and awareness among health care workers was observed post training.